Synthesis and research of new complex compounds of rare earth element nitrates with N-methylglycolurils - Guslyakov, Alexey N.; Razgulyaeva, Yulia Dmitrievna; Turebaeva, Pana Dauletovna; Bakibaev, Abdigali A.; Erkasov, Rakhmetulla Sh (Вестник Томского государственного университета. Химия)
A series of new complex compounds of nitrates of trivalent rare earth elements (lanthanum, cerium, praseodymium, neodymium, samarium, terbium, dysprosium, erbium, ytterbium) with bicyclic bisureas – N-methylglycolurils (N-monomethylglycoluryl, 2,4-N-dimethylglycoluryl, 2,6-N-dimethylglycoluryl, 2,4,6,8-N-tetramethylglycoluryl) as ligands were obtained. IR spectroscopy showed that the rare earth elements (REE) ions are coordinated by two oxygen atoms of two N-methylglycoluryl molecules, three bidentate nitrate anions, and water molecules. N-methylglycolurils realize bidentate, chelating, and bridging functions and tend to form binuclear complexes with rare earth elements. Mass spectrometry with an inductively coupled plasma of synthesized complexes was carried out, and the metal:ligand ratio was ~1:1, respectively. Powder X-ray diffraction allowed us to establish the structures of complex compounds of 2,4,6,8-N-tetramethylglycoluryl with cerium, neodymium, terbium, and dysprosium nitrates. NMR spectroscopy of the obtained complexes was also performed in DMSO-d6 to detect a complex particle in the solution. The resulting complexes are stable in air, however, they are sensitive to trace amounts of water in the solution and are prone to degradation into their original substances.